Orbital Cystic Schwannoma Originating from the Frontal Nerve - Yasuhiko Hayashi; Takuya Watanabe; Daisuke Kita; Yutaka Hayashi; Masayuki Takahira; Jun-ichiro Hamada (Case Reports in Ophthalmological Medicine)
Schwannomas of the orbit are very rare benign neoplasms. Intraorbital cystic schwannomas originating from the frontal nerve are even rarer, with only 1 case reported to date. This is most likely due to the fact that, in most cases, the origin of the orbital schwannoma cannot be identified intraoperatively. The nerve origin is usually speculated from histological examination of the specimen and the postoperative neurological deficits of the patient. Here, we present the case of a 65-year-old woman with a one-month history of exophthalmos, whose orbital cystic lesion was completely removed by microsurgical transcranial operation. Intraoperatively, the continuity between the tumor and frontal nerve was seen macroscopically, leading us to confirm the frontal nerve as an origin of the tumor, which was consistent with the postoperative neurological findings. The diagnosis of the tumor was established as schwannoma from the histological examination. As a differential diagnosis of the orbital cystic lesions, the possibility of schwannomas should be kept in mind.